2011
DOI: 10.1007/s13312-011-0048-3
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral correlates of television viewing in young adolescents in Turkey

Abstract: We evaluated the behavioral effects of television (TV) viewing in 860 young adolescents as reported by parents (n=581) on Child Behavior Checklist (CBCL). The mean duration of TV viewing was 2.32 ± 1.77 hours/day according to parents and 2.08 ± 1.41 hours/day according to self report (r=0.37, P <0.0001). The linear regression analysis revealed a statistically significant relation between socioeconomic status (P=0.019) and aggressive behavior score of CBCL (P=0.016) and parent reported TV viewing hours. Self re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
0
4
0
1
Order By: Relevance
“…The remaining 2 studies for TV viewing (Busch et al 2013;Rosen et al 2014), computer use (Busch et al 2013;Rosen et al 2014), and 1 study for video game use (Busch et al 2013) reported null findings. Similar to the longitudinal studies, associations were not significant across all measures of behavioural conduct/pro-social behaviour for 4 studies (Demirok et al 2012;Ferguson 2011;Ozmert et al 2011;Rosen et al 2014). Additionally 1 study found significant associations for video game use but not for TV viewing or computer use (Rosen et al 2014).…”
Section: S249 Published By Nrc Research Pressmentioning
confidence: 61%
See 2 more Smart Citations
“…The remaining 2 studies for TV viewing (Busch et al 2013;Rosen et al 2014), computer use (Busch et al 2013;Rosen et al 2014), and 1 study for video game use (Busch et al 2013) reported null findings. Similar to the longitudinal studies, associations were not significant across all measures of behavioural conduct/pro-social behaviour for 4 studies (Demirok et al 2012;Ferguson 2011;Ozmert et al 2011;Rosen et al 2014). Additionally 1 study found significant associations for video game use but not for TV viewing or computer use (Rosen et al 2014).…”
Section: S249 Published By Nrc Research Pressmentioning
confidence: 61%
“…Among the cross-sectional studies, higher durations of TV viewing (4/6 studies), computer use (3/5 studies), and video game use (3/4 studies) were significantly associated with unfavourable measures of behavioural conduct/pro-social behaviour (Demirok et al 2012;Ferguson 2011;Ozmert et al 2011;Przybylski 2014;Rosen et al 2014;Shokouhi-Moqhaddam et al 2013;Singh and Yu 2012;van Egmond-Frohlich et al 2012). The remaining 2 studies for TV viewing (Busch et al 2013;Rosen et al 2014), computer use (Busch et al 2013;Rosen et al 2014), and 1 study for video game use (Busch et al 2013) reported null findings.…”
Section: S249 Published By Nrc Research Pressmentioning
confidence: 98%
See 1 more Smart Citation
“…A total of 5599 records were identified after literature search (Figure 1). Fifty-eight cross-sectional studies (1%) were selected from these records for inclusion in this systematic review, of which 30 (52%) were included in the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Christakis ve arkadaşları (21), izlemeye harcanan zamanın ve belirli türden içeriğe maruziyetin çocukların dikkatini olumsuz yönde etkilediğini, davranışsal kontrol sorunlarının meydana gelme riskini arttırdığını göstermiştir. Nathanson ve arkadaşlarının (22), dört yaşındaki çocukların televizyon Günümüzün dijital teknolojisinin karmaşıklığı ve hızla gelişmesi, bu teknolojinin bilimsel araştırmalar için ortaya koyduğu zorluklar göz önüne alındığında, çocukların gelişimi Özellikle uzun saatler şiddet içerikli programlar izleyen çocuklarda saldırganlık düzeylerinin arttığı bildirilmiştir (27,28). Şiddet ve korku barındıran çizgi film programları çocuklar açısından olumsuz sonuçları tetikleyebilir.…”
Section: Karakterleri̇n çOcuklarin Bi̇li̇şsel Ve Fi̇zi̇ksel Geli̇şi̇mi̇ne Etki̇si̇unclassified